Endotoxin neutralization and anti-inflammatory effects of tobramycin and ceftazidime in porcine endotoxin shock - Goscinski, Gunilla (BioMed Central, 2004)
INTRODUCTION: Antibiotics used for treatment of severe bacterial infections have been shown to exert effects on the inflammatory response in addition to their antibacterial effects. The aim of the present study was to investigate whether the biological effects of endotoxin in a porcine model could be neutralized by tobramycin, and whether tobramycin or ceftazidime was able to modulate the inflammatory response. METHOD: Thirteen piglets were subjected to endotoxin infusion at an initial rate of 4 μg/kg per hour, which was reduced to 1 μg/kg per hour after 30 min. Before endotoxin infusion, the animals received saline (n = 4), ceftazidime (n = 5), or tobramycin (n = 4) at clinically relevant doses. Physiological parameters were measured and blood samples were taken hourly for 6 hours for analysis of tumour necrosis factor-α, IL-6 and endotoxin concentrations. RESULTS: All of the animals exhibited physiological signs of severe sepsis without major differences between the groups. Plasma endotoxin concentration was stable after 1 hour. There were no differences in endotoxin concentration or initial tumour necrosis factor-α and IL-6 concentrations between the groups. At 6 hours the IL-6 concentration was significantly lower in the ceftazidime group than in the saline group (P < 0.05), and in both the ceftazidime and the tobramycin groups there were significantly greater reductions from peak values (P < 0.05). CONCLUSION: There was no neutralization of the biological effects of endotoxin in this porcine model. However, our data indicate a possible anti-inflammatory effect exerted by both ceftazidime and tobramycin, which manifested as a significantly greater reduction in IL-6 in comparison with the untreated group.